Efektivitas Penggunaan Media Flipchart dan Media Video Terhadap Peningkatan Pengetahuan Kesehatan Gigi Anak Sekolah Dasar - Jhonny Angky; Saleh, Muhammad; Asriawal; Paembong, Berlin (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Effective dental and oral health education media can have a significant positive impact, such as print media like flipcharts and video media. This study aims to evaluate the effectiveness of using flipchart and video media in improving elementary school children's knowledge of dental health. This research employs a quantitative approach using a one-group pretest-posttest design with a pre-experimental method. The research sample consisted of 250 students from Tidung State Elementary School, selected through a random sampling technique using the lottery method, and divided into two groups: one using flipchart media and the other using video media. Data were analyzed using the Wilcoxon test. The results showed that after the intervention, video media had a greater impact than flipchart media, with a significance value of 0.000 < 0.05. This indicates that video media is more effective than flipchart media in increasing knowledge about dental and oral health.